1994
DOI: 10.1007/bf00119866
|View full text |Cite
|
Sign up to set email alerts
|

Common prevalence of alanine and glycine in mobile reactive centre loops of serpins and viral fusion peptides: Do prions possess a fusion peptide?

Abstract: Serpin reactive centre loops and fusion peptides released by proteolytic cleavage are particularly mobile. Their amino acid compositions reveal a common and unusual abundance of alanine, accompanied by high levels of glycine. These two small residues, which are not simultaneously abundant in stable helices (standard or transmembrane), probably play an important role in mobility. Threonine and valine (also relatively small amino acids) are also abundant in these two kinds of peptides. Moreover, the known 3D str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
7
14
0
Order By: Relevance
“…We would like to re-emphasise the striking similarity between the amino acid composition of the prion 110 -135 segment and those of viral fusion peptides and reactivecenter loops of serpins [13,27,41]. This prion segment appears to meet the global amino acid composition of canonical fusion-like and mobile peptides [e. g. the human prion 119 -137 segment GAVVGGLGGYML-GSAMSRP globally matches quite well the 356 -373 reactive loop of human plasminogen activator inhibitor GTVASSSTAVIVSARMAP).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We would like to re-emphasise the striking similarity between the amino acid composition of the prion 110 -135 segment and those of viral fusion peptides and reactivecenter loops of serpins [13,27,41]. This prion segment appears to meet the global amino acid composition of canonical fusion-like and mobile peptides [e. g. the human prion 119 -137 segment GAVVGGLGGYML-GSAMSRP globally matches quite well the 356 -373 reactive loop of human plasminogen activator inhibitor GTVASSSTAVIVSARMAP).…”
Section: Resultsmentioning
confidence: 86%
“…We previously reported that the sequence of the PrP C globular domain which, at first glance, appears as conventional as any other globular domain, possesses in its N terminus a peculiar peptide (ranging from amino acids 110 to 135). The global amino acid composition of this peptide indeed shares similarities with those of fusion peptides from viral envelope glycoproteins and of reactive loops of serine protease inhibitors (serpins) [13]. These fusion peptides and serpin reactive loops are characterized by a high content of small amino acids (alanine, glycine, threonine), are intrinsically flexible [14 -19], and are associated with large 3D conversions of their support proteins, leading to more stable structures that allow the achievement of their respective biological functions.…”
Section: Introductionmentioning
confidence: 89%
“…One of the reasons for the shallower active site pocket in HjCel3A is that two loops that connect ␣-helix Asn 24 (64,65). The two glycine residues at these positions could therefore potentially serve as two hinges for opening and closing of this loop and could potentially play a role in the specificity and/or activity of the enzyme for the substrate.…”
Section: Effect Of Hjcel3a On Cellulose Degradation By Cellulasementioning
confidence: 99%
“…Transition from PrP c to PrP Sc has been shown to be linked to an increase in the i-sheet content of the protein [20]. Several years ago, we noticed that the global composition of the third region is reminiscent of that of fusion peptides from viral envelope glycoproteins (the fusion peptide of HTLV-I is shown below), suggesting that this region, like fusion peptides, may also be structurally highly mobile [21]. Both peptides are hydrophobic and especially rich in small amino acids such as glycine and alanine.…”
Section: Hca As a Tool To Compare Protein Sequences Within And Below mentioning
confidence: 99%